Critical thinking skills of nursing students: Observations of classroom instructional activities - Christian Makafui Boso; Anita S. van der Merwe; Janet Gross (Wiley, 2020)
Abstract Aim Critical thinking (CT) is vital for nursing practice. Nursing schools should provide learning experiences that enable nursing students to acquire CT skills. Yet, these authors are not aware of any study that has directly observed instructional activities related to CT skills acquisition in the classroom environment. The aim of this study was to explore instructional activities in the classroom environment in relation to acquisition of CT skills of students. Design Qualitative non‐participant observation. Methods Using a purposive sampling, 10 classroom teaching sessions were observed and mediating factors of CT skills acquisition of students noted. Data were analysed thematically. Data were collected from October-December 2017.  Results Three key themes of instructional activities relating to acquisition of CT skills of students emerged, namely educators' behaviour, students' characteristics and university‐wide factors/administrative support. Class sizes ranged from 34-162 students with an average of 95.